“Screw you, this is a cheerful place”: Platformized violence among positive-vibe Reddit communities - Morales Velasquez, Esteban (AoIR Selected Papers of Internet Research, 2026)
While Reddit is often associated with toxic techno-cultures, platformized violence is not confined to explicitly harmful spaces—it also emerges in communities dedicated to fostering ‘good vibes.’ In this context, this paper examines how platformized violence operates in four of Reddit’s most popular positive-vibe communities. Using digital ethnography, I analyze how harmful speech manifests in these spaces and how community dynamics shape its function and visibility. Findings reveal two key mechanisms: targets and visibility. These two mechanisms show that, while platformized violence is used to reinforce oppression through insults and exclusion, it is also deployed as a strategy of ‘punching up’—attacking those in positions of power to defend marginalized groups. Additionally, platform affordances such as moderation and downvoting influence the visibility of platformized violence, sometimes mitigating harm and other times weaponizing obscurity. These findings challenge simplistic understandings of platformized violence, demonstrating its dual role in both sustaining and disrupting online toxicity. This study highlights the need for nuanced governance strategies that balance community well-being with the complexities of online harm.